2009
DOI: 10.1111/j.1439-0329.2008.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Botryosphaeriaceae associated with Eucalyptus canker diseases in Colombia

Abstract: The identities of Botryosphaeriaceae causing cankers on Eucalyptus in Colombia were investigated using morphological and DNA sequence comparisons. The pathogenicity of the species was also assessed on 42 Eucalyptus grandis clones planted at four different sites. Two species of the Botryosphaeriaceae were found to occur on E. grandis in Colombia. Neofusicoccum ribis was the more common species, and also the most pathogenic. Botryosphaeria dothidea was found only in one zone of Colombia, and was also less pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
3
29
0
1
Order By: Relevance
“…After its first description from kiwifruit in New Zealand (Pennycook & Samuels 1985), this species has been recorded from more than 90 hosts, mostly woody angiosperms, across the globe (Phillips et al 2002;Gure et al 2005;, Sakalidis et al 2011). On Eucalyptus, it is commonly reported as a cause of canker and die-back (Nakabonge 2002;Ahumada 2003;Gezahgne et al 2004;Barber et al 2005;Mohali et al 2006;Rodas et al 2009;Chen et al 2011;Iturritxa et al 2011;Pillay et al 2013). In South Africa, Neofusicoccum parvum is also known from native Myrtaceae, including Heteropyxis natalensis and Syzygium cordatum (Smith et al 2001;Slippers et al 2004;Pavlic et al 2007, Pillay et al 2013, Pavlic-Zupanc et al 2015.…”
Section: Discussionmentioning
confidence: 98%
“…After its first description from kiwifruit in New Zealand (Pennycook & Samuels 1985), this species has been recorded from more than 90 hosts, mostly woody angiosperms, across the globe (Phillips et al 2002;Gure et al 2005;, Sakalidis et al 2011). On Eucalyptus, it is commonly reported as a cause of canker and die-back (Nakabonge 2002;Ahumada 2003;Gezahgne et al 2004;Barber et al 2005;Mohali et al 2006;Rodas et al 2009;Chen et al 2011;Iturritxa et al 2011;Pillay et al 2013). In South Africa, Neofusicoccum parvum is also known from native Myrtaceae, including Heteropyxis natalensis and Syzygium cordatum (Smith et al 2001;Slippers et al 2004;Pavlic et al 2007, Pillay et al 2013, Pavlic-Zupanc et al 2015.…”
Section: Discussionmentioning
confidence: 98%
“…A number of pathogenicity trials have shown variable degrees of resistance or tolerance of Eucalyptus clones to infection by species of Botryosphaeriaceae (Mohali et al 2009, Rodas et al 2009). Such trials are quite easily implemented via routine stem inoculations and subsequently measuring the resulting lesions that develop after a few weeks.…”
Section: Controlmentioning
confidence: 99%
“…was thought to be common on Eucalyptys, but DNA sequence comparisons have now shown that many of the early identification were possibly incorrect and that these species are rare on Eucalyptus. Earlier reports of these fungi probably represent species such as N. parvum and others (Slippers et al 2004a, b;Burgess et al 2005;Rodas et al 2009). …”
mentioning
confidence: 99%
“…Neofusicoccum parvum has previously been reported as causing canker symptoms of Eucalyptus species in many parts of the world, including Australia, Chile, China, Ethiopia, Indonesia, South Africa, Uganda, Uruguay, Venezuela (Rodas et al 2009). Previous Botryosphaeria dothidea (Moug.…”
mentioning
confidence: 99%